Re-thinking the Lower-middle Level of Administration in Hungary with Particular Reference to the Web 3.0. Era - Buskó, Tibor László (Public Governance, Administration and Finances Law Review, 2021)
This paper will evaluate the current situation and role of the Hungarian (administrative) lower-middle level and make projections about its future. Centralisation efforts since 2010 have had a non-negligible impact on the administrative and non-administrative (common institution maintenance, micro-regional development policy) tasks assigned to the lower-middle level. However, it may be argued that the transition to the Web 3.0 era – the era of the most advanced, most intelligent and customised web technologies – may put such centralisation efforts into a new context. Revitalisation of formations similar to the multi-functional micro-regional associations of local self-governments which largely disappeared after 1 January 2013 may be justifiable in the forthcoming period in order to promote local synergies. If this is correct, a rethink of the public administration system at the lower-middle level may become a very important task for the public administration as along with regional discourse.